Sofosbuvir and velpatasvir with or without voxilaprevir in direct‐acting antiviral‐naïve chronic hepatitis C: patient‐reported outcomes from POLARIS 2 and 3. Issue 2 (27th November 2017) - Younossi, Z. M.; Stepanova, M.; Jacobson, I. M.; Asselah, T.; Gane, E. J.; Lawitz, E.; Foster, G. R.; Roberts, S. K.; Thompson, A. J.; Willems, B. E.; Welzel, T. M.; Pearlman, B.; et al.
Summary: Background: Chronic hepatitis C infection leads to impairment of patient‐reported outcomes (PROs). Treatment with direct‐acting antiviral regimens results in short‐ and long‐term improvement of these outcomes. Aim: To assess PROs in patients treated with a newly developed direct‐acting antiviral, a fixed‐dose combination of sofosbuvir/velpatasvir (SOF/VEL) with/without voxilaprevir (VOX). Methods: The PRO data were collected from participants of POLARIS‐2 and POLARIS‐3 clinical trials (DAA‐naïve, all HCV genotypes). Participants self‐administered SF‐36v2, FACIT‐F, CLDQ‐HCV and WPAI:SHP instruments at baseline, during treatment, and in follow‐up. Results: Of 1160 patients, 611 received SOF/VEL/VOX and 549 received SOF/VEL (52.8 ± 11.0 years, 55.9% male, 75.4% treatment‐naïve, 33.9% cirrhotic). The sustained viral response at 12 weeks (SVR12) rates were 95%‐98%. During treatment, improvements in most PRO scores were significant (all but one P  < .01) and ranged from, on average, +2.3 to +15.0 points (on a 0‐100 scale) by the end of treatment. These improvements were similar between SOF/VEL/VOX and SOF/VEL arms (all P  > .05). After treatment discontinuation, patients treated with both regimens achieved significant and clinically meaningful PRO gains (+2.7 to +16.7 by post‐treatment week 12, +3.9 to +20.1 by post‐treatment week 24; all but one P  < .001). Multivariate analysis showed that depression, anxiety and cirrhosis were the most consistent independent predictors of PRO impairment while no association of PROs with the treatment regimen choice was found (all P  > .05). Conclusions: The pan‐genotypic regimens with SOF/VEL with or without VOX not only have excellent efficacy and safety, but also significantly positively impact patients' experience both during treatment and after achieving sustained virologic response in DAA‐naïve patients with HCV. Abstract : Linked Content This article is linked to Younossi and Sanagapalli and Danta papers. To view these articles visithttps://doi.org/10.1111/apt.14481 andhttps://doi.org/10.1111/apt.14467 .